Geochemical Characterization of the Uranium Mineralization in the Cenozoic Basin in the Central Anatolia, Turkey - Alcicek, O. N.; Kalender, L. (Pleiades Publishing Inc, 2019)
Uranium contents were measured in the siltstones and siliceous limestone interbeds within sandstone of Kubaca member of the Eocene of Ayhan formation, with chemical values ranging from 175 to 2537 ppm and radiometric values ranging from 85.40 to 660.40 cps. The highest chemical values of uranium and Th/U were obtained from the siltstones. Mineralogical studies were also conducted, and these indicated that uranium is associated with fluorapatite and hydroxyapatite in the siltstone and as discrete rutherfordine in fractures of siliceous limestone. The uranium contents in the siltstones are higher than those in the siliceous limestones due to the cation-exchange capacity and adsorption of smectite/kaolinite group clay minerals. The D-factor determination of the equilibrium state of the studied rocks indicated that chemically analyzed uranium values are greater than radiometrically determined uranium values, reflecting a disequilibrium state characterized by the addition of uranium into the system. The study shows two types of the uranium mineralization: (1) syngenetic phosphate cement controlled and (2) epigenetic, fluid driven, fracture controlled. The potentiality of the area with respect to uranium is enhanced in view of the addition of uranium into fractures and fault planes, after remobilization from the overlying phosphatic siltstone unit and other deep-seated sources.
Keywords: Dadagi; geochemistry; uranium mineralizations